The neuroprotective effect of quetiapine in critically ill traumatic brain injury patients. Issue 4 (October 2020) - Asmar, Samer; Lokhandwala, Adil; Richards, Joseph; Bible, Letitia; Avila, Mauricio; Castanon, Lourdes; Ditillo, Michael; Douglas, Molly; Joseph, Bellal
Abstract : INTRODUCTION: Quetiapine is an atypical antipsychotic commonly used in critical care. Cellular and animal models demonstrated its novel anti-inflammatory properties in traumatic brain injury (TBI). Our study aimed to assess the effect of quetiapine on outcomes in critically ill TBI patients. We hypothesize that quetiapine improves neurological outcomes. METHODS: The Multiparameter Intelligent Monitoring in Intensive Care database was queried, and all adult (age, ≥18 years) isolated TBI patients (extracranial Abbreviated Injury Scale, < 2) admitted to the intensive care unit for a period of >48 hours. Patients were stratified into quetiapine (+) and no-quetiapine (−) groups. Propensity score matching was performed (1:2 ratio). Outcome measures were intensive care unit length of stay, discharge Glasgow Coma Scale (GCS), and mortality. A subanalysis was performed for patients who underwent intracranial pressure (ICP) monitoring to ascertain the effect of quetiapine dose on ICP, and cerebral perfusion pressure (CPP). Survival curves and regression analyses were performed. RESULTS: A matched cohort of (quetiapine, 116 vs. no-quetiapine, 232) patients was obtained. Mean ± SD age was 65 ± 21 years, median head Abbreviated Injury Scale was 3 (3–4), and median GCS was 10 (9–16). The median quetiapine dose given was 50 (25–125) mg. Patients who received quetiapine had lower mortality (17.2% vs. 27.6%; p = 0.03) and a higher median GCS at discharge (12 [11–14] vs. 11 [10–13]; p < 0.04) but no difference in intensive care unit length of stay (4.1 days vs. 4.7 days; p = 0.75) or discharge to skilled nursing facility (34.5% vs. 31.9%; p = 0.63). On subanalysis of patients who received quetiapine, 40% had ICP monitoring. Higher doses of quetiapine were independently associated with progressively lower ICP ( β = −0.022 mm Hg/mg of quetiapine; p = 0.01) and higher CPP ( β = 0.031 mm Hg/mg quetiapine; p = 0.01). CONCLUSION: Quetiapine may decrease mortality and improve neurological outcomes in critically ill TBI patients. It has a dose-dependent effect to decrease ICP and increase CPP. Quetiapine may be a potential therapeutic modality in critically ill TBI patients, but further studies are required to explore these mechanisms. LEVEL OF EVIDENCE: Systematic Review, level III. Abstract : Supplemental digital content is available in the text.